A Posthuman Gothic Tale: Kelly Link’s “Two Houses” - Muñoz-González, Esther (International Journal of English Studies, 2024)
It is at the intersection of Posthuman thought, Gothic narratives, and the New Weird mode where “Two Houses” from Kelly Link’s Get in Trouble (2016) can be framed. In the story, six female astronauts alternate years of hibernation and moments of wakefulness in search of a habitable planet. The House of Secrets spaceship is controlled by the AI Maureen. Isolated in space, the astronauts amuse themselves by telling ghost stories. Through the stories, the reader is gradually dislocated from the recognizable landscape of a technologically plausible speculative fiction story to be plunged into a Gothic world of murder, haunted houses, and ghosts. The purpose of this paper is to trace the intersection of Posthuman thought and Gothic characteristics in the story to discuss the slippery relationship between what we believe we are and what we actually are.